Study on Application of Uneven Waste Slag in Secondary Dam of Qianjiang River at Datengxia Gorge Water Conservancy Project - FAN Suixing; TU Xiaoxia (Renmin Zhujiang)
The shell of the secondary dam of Qianjiang River at Datengxia Gorge is filled with waste slag materials with a large change in material properties and uneven gradation and mud content.The quality of dam materials is difficult to control,and there is no corresponding control standard in the specification.In the application process of waste slag materials,according to the results of investigation and tests of dam materials,the design unit adopts the comprehensive method of material property analysis,compaction condition analysis,filling standards,and joint control of construction parameters to design and control the dam material.Through operation tests,the application of waste slag materials has achieved good results.This method expands the application scope of the earth-rock and also provides a reference for the application and control of similar dam materials in earth-rock dam projects.